Предмет: Алгебра, автор: Аноним

Упростите выражение ctgt+tg(-t)/cost+sin(-t)+tg(-t)/sint

Приложения:

Ответы

Автор ответа: NeZeRAvix
0
 dfrac{ctgt+tg(-t)}{cost+sin(-t)}+ dfrac{tg(-t)}{sint} = \  \ = dfrac{ frac{cost}{sint}- frac{sint}{cost}  }{cost-sint}- dfrac{ frac{sint}{cost} }{sint}   = \  \ = dfrac{ frac{cos^2t-sin^2t}{sintcost} }{cost-sint}- dfrac{1}{cost} = \  \ =  dfrac{cos^2t-sin^2t}{sintcost(cost-sint)} - dfrac{1}{cost}= \  \ =  dfrac{(cost-sint)(cost+sint)}{sintcost(cost-sint)}- dfrac{1}{cost}= \  \ = dfrac{cost+sint-sint}{sintcost}= \  \ = dfrac{cost}{sintcost}= \  \ = dfrac{1}{sint}
Похожие вопросы
Предмет: Математика, автор: oryngalidamira0